Closed cycle of air-steam mixture the drying section of paper machine - V. G. Kazakov; E. N. Gromova (Известия высших учебных заведений: Проблемы энергетики)
The energy efficiency of the drying section of paper machine is determined by the technology of heat flows arrangements in it. Paper drying is the most energy-consuming stage of paper production. The thermal mode of the drying section is provided by the steam condensate system which is a part of it. Analysis of exergy increments shows that almost all elements of the drying thermal process are characterized by low exergy efficiency. The main ways for increasing the degree of thermodynamic perfection of the processes occurring in the drying section of the paper machine are identified based on the exergy analysis. It is assumed that the deep internal heat recovery of the steam-air mixture for heating the source air will increase the exergy efficiency of the heat recovery plant and reduce heat removal to the environment. The effectiveness of development and implementation of a closed cycle use of steam-air mixture in the drying section was examined. Building a closed cycle provides that the air mainly has a process duty, that is, it is a transport agent for the transfer of moisture and heat along a closed circuit. The calculations show that the exergy efficiency of the processes in the recovery unit of the drying section of the paper machine of the existing production is 28.6% against 66.29% for the proposed method.